2011
DOI: 10.1056/nejmoa1103070
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Element Necessary for Fetal Hemoglobin Silencing

Abstract: BACKGROUND An improved understanding of the regulation of the fetal hemoglobin genes holds promise for the development of targeted therapeutic approaches for fetal hemoglobin induction in the β-hemoglobinopathies. Although recent studies have uncovered trans-acting factors necessary for this regulation, limited insight has been gained into the cis-regulatory elements involved. METHODS We identified three families with unusual patterns of hemoglobin expression, suggestive of deletions in the locus of the β-gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
150
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 173 publications
(157 citation statements)
references
References 29 publications
4
150
1
2
Order By: Relevance
“…However, BCL11A does not bind detectably to the γ-globin promoter in erythroid chromatin, suggesting that its mode of action is more complex than simply blocking transcription at the proximal promoter. This observation is consistent with a role of BCL11A in promoting long-range chromosomal interactions within the β-globin locus (6,7,9). Therefore, in an effort to elucidate further the precise molecular mechanisms by which BCL11A coordinates the switch, it is relevant to identify systematically BCL11A-interacting partner proteins, and use functional and genetic approaches to assess their individual roles in HbF regulation and erythroid cell maturation.…”
supporting
confidence: 76%
“…However, BCL11A does not bind detectably to the γ-globin promoter in erythroid chromatin, suggesting that its mode of action is more complex than simply blocking transcription at the proximal promoter. This observation is consistent with a role of BCL11A in promoting long-range chromosomal interactions within the β-globin locus (6,7,9). Therefore, in an effort to elucidate further the precise molecular mechanisms by which BCL11A coordinates the switch, it is relevant to identify systematically BCL11A-interacting partner proteins, and use functional and genetic approaches to assess their individual roles in HbF regulation and erythroid cell maturation.…”
supporting
confidence: 76%
“…By mapping a variety of deletions within the human b-globin locus that either result in db-thalassemia, with modest increases in HbF and some remaining globin chain imbalance present, or HPFH, with robust increases in HbF and balanced globin chain synthesis, it was shown that an N3-kb region upstream of the d-globin gene is necessary for silencing of the g-globin genes ( Fig. 2) (Sankaran et al 2011c). Interestingly, this region harbors binding sites for BCL11A, along with its partners such as GATA1 and HDAC1.…”
Section: The Promise Of Improved Therapies Through Molecular Studiesmentioning
confidence: 99%
“…However, there are examples where aspects of mouse erythropoiesis are inconsistent with human erythropoiesis. For example, humans express a fetal hemoglobin not found in the mouse, and their globin gene regulation pattern differs significantly (5)(6)(7). Mutations that impair erythropoiesis in humans are often not faithfully recapitulated in mouse models (8)(9)(10)(11).…”
mentioning
confidence: 99%